Regulatory mechanisms for underground waste disposal in Nigeria: review and implications for environmental management - Irwin Anthony Akpoborie (Journal of Applied Sciences and Environmental Management)
The Federal Ministry of Environment and the Department of Petroleum Resources control underground disposal of wastes in Nigeria with three principal regulations: Guidelines and Standards for Environmental Pollution Control in Nigeria, National Guidelines on Waste Disposal through Underground Injection and the Environmental Guidelines and Standards for the Petroleum Industry of Nigeria. The review shows that in general, the design and materials specifications for injection wells, monitoring wells and landfills lack precision and as a result allow too much latitude in interpretation. Furthermore, the laws place inordinate reliance on waste facility owners to ascertain crucial parameters for example, well casing integrity and in the case of landfills, liner integrity which regulators do not have the capacity or resources to verify. This problem recurs in all aspects of the regulations including environmental impact assessments and environmental management plan monitoring. The regulations also allow no role for resident communities in environmental monitoring. Runoff injection into near surface aquifers is unregulated as it is not covered by existing rules. Therefore, regulatory reforms are needed if aquifers are to be adequately protected should underground waste disposal gain universal acceptance and applicability in Nigeria’s emerging waste management industry. It is recommended that the reform agenda be driven by the Federal Ministry of Water Resources which currently plays no active role in underground waste disposal control although empowered by the Water Resources Act to manage and protect the nation’s water resources. @JASEM